Profil kemampuan peserta didik kelas v sekolah dasar dalam mengklasifikasi ragam instrumen gamelan Jawa di kota Surakarta - Marsudi, Mahawi; Karsono, Karsono; Rintayati, Peduk (Universitas Sebelas Maret, 2025)
Abstract. This research aims to determine the profile of class V students' abilities in classifying various Javanese gamelan musical instruments in the city of Surakarta in 2024. This research uses a quantitative approach with a survey method. The population of this study was fifth grade students of state elementary schools in the city of Surakarta in 2024. The sampling technique used was purposive sampling combined with cluster random sampling. The data collection technique uses multiple choice tests. The validity of this research instrument uses content validity using the Aiken's V formula, while for reliability it uses the Cronbach's Alpha formula. The data analysis technique in this research uses descriptive statistical analysis. This data analysis technique is carried out to find the number, median, mode, standard deviation, minimum and maximum. The results of this research are that the ability of class V students to classify based on how to play and the materials for making Javanese gamelan instruments is in the